Alkaline pre-treatments and different parameters as facilitators for obtaining cellulose nanofibrils - Dias, Matheus Cordasso (2017)
Cellulose nanofibrils are promising to replace materials of synthetic origin and in macroscale due to their differentiated properties and the fact of being of natural and renewable origin. However, it presents as disadvantage the high energy consumption that is necessary for its production, being this the main limiting factor to produce cellulose nanofibrils on an industrial scale. The objective of this work was to evaluate the effect of the concentration variation (5 and 10%) and the reaction time (1 and 2 h) of alkaline pre-treatments of cellulosic fibers from commercial bleached pulps of Eucalyptus sp. and Pinus sp. as facilitators in mechanical defibrillation. The pre-treatments were performed with sodium hydroxide (NaOH) solutions in 5% concentration and 2 h of reaction and 10% with 1 and 2 h of reaction. The nanofibrils were obtained by means of a mechanical process using a grinder and the energy consumption during the defibrillation process of the cellulosic fibers for each pre-treatment was evaluated. Chemical and morphological analyzes of the fibers were conducted without and with pre-treatments. It was observed that the alkaline pre-treatment was efficient in the removal of the hemicelluloses, especially of the xyloses where the concentration of the alkaline solution and the reaction time influenced the amount of extractives, lignin and carbohydrates removed. The pre-treatments also caused a decrease in the length and diameter of the fibers mainly in Eucalyptus pulps. The degree of defibrillation was also influenced by the removal of hemicelluloses, there was less defibrillation when excessive removal occurred (hemicelluloses in the range of 2 to 7%). The treatment of the fibers with NaOH 5% 2 h was shown to increase the water retention value (WRV) and effective to facilitate the obtaining of cellulose nanofibrils, with lower energy consumption. This treatment caused partial removal of hemicellulose (keeping them in a range of about 8.5 and 12%) and led to nanofibrils with lower diameter. With the passes through the grinder, cellulose nanofibrils with average diameters of 42 ± 16 nm and 36 ± 14 nm were obtained for the controls; 25 ± 13 nm and 22 ± 11 nm for treatments with NaOH 5% 2h for Eucalyptus and Pinus respectively. Treatments with higher concentrations of NaOH were not effective for the defibrillation of the cellulosic fibers. Fibers treated with NaOH 5% 2 h also promoted a lower energy consumption during the mechanical defibrillator, where for Eucalyptus energy savings were around 23% and 25% for Pinus. The results show that the hemicelluloses contents of the fibers influence the degree of defibrillation and that their excessive removal of the fiber composition impairs the process of obtaining the nanofibrils and the treatment of the fibers with 5% NaOH solution 2 h has been effective as a facilitator of defibrillation process. The present work contributes with information for the optimization of the process of obtaining nanofibrils on an industrial scale and its application in new products for the most diverse uses. We also sought to contribute to the understanding of the inherent chemical and morphological characteristics of the fibers that interfere in the mechanical defibrillation process.